Acute myelopathy associated with primary infection with human immunodeficiency virus. Issue 6565 (17th January 1987) - Denning, D W; Anderson, J; Rudge, P; Smith, H
Abstract : A 29 year old white homosexual man presented with a two and a half week history of severe sore throat, fever, and extreme fatigue. His symptoms did not respond to antibiotics. He had mild bilateral conjunctivitis, a rash over his chest and back, and enlarged lymph nodes, but examination of the nervous system yielded normal results. He had low total white cell and platelet counts. The results of enzyme linked immunosorbent assay for human immunodeficiency virus (HIV) were equivocal when HIV IgM was detected in serum. Despite treatment with ampicillin his temperature remained high and he developed abnormal neurological signs, including a paraparesis and hyperreflexia of the arms. HIV was isolated from lymphocytes from blood and cerebrospinal fluid. Over the next six weeks the patient improved and was discharged. Two months later abnormal neurological signs persisted in his legs. Although various neurological syndromes associated with seroconversion to HIV have been described, this is probably the first report of a patient with myelopathy at the time of seroconversion.